Behavior of the solid isolations of power transformers under environmental not controlled conditions - Jiménez-Araya, Gustavo (2016)
One of the important aspects in the useful life of a power transformer, is the conservation of the solid and liquid isolations. These will have to remain complete before the presence of dampness and pollutants. One tries to support the staunchness inside this one in order to preserve his integrity. The principal aim of this investigation is to study and to analyze the deterioration of the solid isolations in power transformers under environmental not controlled conditions. Hereby one wants to verify by means of the Isolation test and index of polymerization the existence of some type of deterioration in the insulating solid materials that were sampled. Likewise, gives the estimated one of the degree of percentage deterioration of the solid low isolation conditions of temperature and relative dampness not controlled. The fundamental problem of this one is the deterioration of the insulation properties and mechanical of the insulating paper in the time. This will do that before a short circuit, the insulating paper is unable to support and to be the beginning of a fault.